2018
DOI: 10.1016/j.ijpharm.2017.12.042
|View full text |Cite
|
Sign up to set email alerts
|

Zinc delivery from non-woven fibres within a therapeutic nipple shield

Abstract: A Therapeutic Nipple Shield (TNS) was previously developed to respond to the global need for new infant therapeutic delivery technologies. However, the release efficiency for the same Active Pharmaceutical Ingredient (API) from different therapeutic matrices within the TNS formulation has not yet been investigated. To address this, in-vitro release of elemental zinc into human milk from two types of Texel non-woven fibre mats of varying thickness and different gram per square meter values, placed inside the TN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Previous studies have explored the putative benefits of solid formulations during breastfeeding in low resource settings [15]. A variety of compounds and drugs have been studied using an in-vitro model including zinc [3,16]. Such delivery of zinc could help in the prevention and treatment of diarrheal disease and pneumonia which are significant causes of child mortality and morbidity [16], particularly since manufacturing costs for unbranded nipple shields are considered compatible to oral syringes and applicable for low and middle income countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have explored the putative benefits of solid formulations during breastfeeding in low resource settings [15]. A variety of compounds and drugs have been studied using an in-vitro model including zinc [3,16]. Such delivery of zinc could help in the prevention and treatment of diarrheal disease and pneumonia which are significant causes of child mortality and morbidity [16], particularly since manufacturing costs for unbranded nipple shields are considered compatible to oral syringes and applicable for low and middle income countries.…”
Section: Discussionmentioning
confidence: 99%
“…However recent studies have also highlighted the emotional and practical challenges for many parents, of treating infants with liquid formulations as many infants demonstrate aversive behavior towards drug delivery from oral syringes [2]. The potential alternative of solid formulation drug delivery during breastfeeding was previously shown during in-vitro (lab-based) studies using a breastfeeding simulation apparatus [3,4]. Now, this study aimed to evaluate the feasibility and acceptability of solid formulation delivery in a clinical setting with recruited infants while breastfeeding.…”
Section: Introductionmentioning
confidence: 99%
“…Dosing devices for this age group mainly involves the use of an oral syringe or dropper though both have significant issues in terms of accuracy [40,41]. Therapeutic nipple shield [42,43] and medicine dispensing pacifiers [44,45] have been suggested for home use, but these are as yet experimental. In hospitalised patients, enteral tubes can be used for the administration of oral medicines where liquids (ideally solutions rather than suspensions) are the preferred dosage forms.…”
Section: Formulation Considerationsmentioning
confidence: 99%
“…In-vitro studies have previously demonstrated the potential of drug administration using a breastfeeding simulation apparatus. [3,4] Qualitative studies within our Neonatal Unit also demonstrated parents’ and nursing staff’s support for such an intervention, indicating that it could help foster mother-infant bonding and encourage parental empowerment. [2]…”
Section: Introductionmentioning
confidence: 99%